A STUDY TO ASSESS KNOWLEDGE, ATTITUDE AND PRACTICE ON BREAST CANCER AMONG WOMEN IN GOVERNMENT GENERAL HOSPITAL - G, DIVYA; CHOUDHARY DG, PRAVALLIKA; KUMAR J, KARUN; A, PRAVEEN; PN, SMITHA; R, LAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Breast cancer is the most frequent cancer in women worldwide and it accounts for 27% of all cancer cases among women in India. This study aims to assess the awareness of the patients regarding the breast cancer and also to check their knowledge toward the symptoms of breast cancer as well as the breast self-examination process. This study also determines the attitude of patients regarding the breast cancer and breast self-examination. Methods: A prospective educational study was done using a pre-designed questionnaire on 523 patients in a tertiary care teaching hospital for a period of 6 months. All women greater than 20 years admitted in the Department of General Medicine and General Surgery in-patient female ward of SVRRGGH were included in the study. Results: Out of 523 women, a greater proportion respondents 515 (98%) had poor knowledge of breast cancer. Two hundred and eighty-one (53%) show positive attitude while 225 (43%) show neutral attitude and 17 (4%) show negative attitude toward breast cancer. Only 18 (0.3%) know how to perform breast self-examination while the remaining patients have never performed the breast self-examination. Two hundred and one (38%) have agreed to consult a doctor if they found any lumps in the breast whereas the remaining did not respond. After the counseling session with patients, their knowledge regarding the above problems related to breast cancer has significantly increased. Conclusion: Majority of the participants had poor knowledge of breast cancer as well as low level of practice of breast cancer screening procedures. However, patients do have a positive attitude toward the breast cancer which can help to detect the cancer in early stages. Hence, a greater focus on providing breast cancer education programs can create awareness among women in respect to screening programs which, in turn, can decrease the risk of death due to its late discovery.